Effect of low-temperature plasma-treated bentonite on rubber compounds properties - Mičicová, Zuzana; Pajtášová, Mariana; Ondrušová, Darina; Božeková, Slavomíra; Ďurišová, Silvia; Janík, Róbert (Polimery, 2024)
The influence of low-temperature plasma modification of bentonite on the dynamic-mechanical properties and vulcanization of rubber mixtures was examined. EDX, FTIR and TGA analysis were used to evaluate the filler. IR spectra of modified bentonite indicate lower intensity of the bands associated with OH groups and water. TGA confirms a smaller weight loss of samples subjected to plasma treatment, which also proves a lower water content in the mineral, confirming the effectiveness of the plasma treatment used.